Carter Dimension Analysis of Customer Satisfaction In Improving Electronic Word Of Mouth (E-Wom) In Bank Syariah Mandiri Customers. - Asmuni Asmuni; Isnaini Harahap; Lenny Menara Sari Saragih (International Journal of Artificial Intelligence Research, 2022)
This study aims to analyze the effect of CARTER dimensions consisting of tangible, assurance, reliability, tangible, empathy and responsiveness on customer satisfaction at Bank Syariah Mandiri in Medan City. electronic word of mouth. Respondents in this study were customers of Bank Syariah Mandiri in Medan City who were Muslim and used Mobile Banking. A total of 300 questionnaires were distributed, there were 220 questionnaires that met the criteria. So that the data can be processed as many as 220 samples. The analysis technique uses Structural Equation Modeling with AMOS.The results show that the Compliance dimension has a positive and significant effect on customer satisfaction at Bank Syariah Mandiri in Medan City, the assurance dimension has a significant positive effect on customer satisfaction at Bank Syariah Mandiri in Medan City, the reliability dimension has a positive direction but does not significantly affect customer satisfaction at Bank Syariah Mandiri in Medan. Medan City, the tangible dimension is the largest dimension that has a positive and significant effect on customer satisfaction of Bank Syariah Mandiri in the City, the dimension of empathy has a positive and significant effect on customer satisfaction of Bank Syariah Mandiri in the City, the dimension of responsiveness has a positive and significant effect on customer satisfaction of Bank Syariah Mandiri in Medan city. The variable of customer satisfaction has a positive and significant effect on electronic word of mouth on Bank Syariah Mandiri customers in Medan City. The Sobel test conducted shows that customer satisfaction has a significant effect as a mediator between the tangible, assurance, tangible, empathy and responsiveness dimensions and Electronic Word of Mouth.